Is it mastalgia or myofascial pain? A clinical confusion - Sibel MANDIROĞLU; Ulvi Murat YÜKSEL; Sibel ÜNSAL DELİALİOĞLU and Lütfi DOĞAN (Archives of Rheumatology, 2021)
Objectives: This study aims to investigate the frequency of myofascial pain syndrome (MPS) and its characteristics in mastalgia patients. Patients and methods: The localization of pain, age, education, menopausal status, hormone replacement and employment status, and existence of comorbid diseases were reviewed on consecutive 131 female mastalgia patients (mean age 43.3±9.4 years; range, 18 to 75 years) in this prospective study conducted between June and December 2019. A total breast pain index (IBP) was obtained and mastalgia was classified according to these scores as mild, moderate, and severe. Patients were divided into four diagnostic groups of MPS, cyclic mastalgia, fibrocystic breast disease, and mastitis. Results: The total IBP was significantly higher in MPS group (129.2±49.5) than in cyclic mastalgia group (98.3±11.9) (p<0.05). However, it was significantly higher in mastitis group (230.7±17.6) compared to MPS group (p<0.05). The fibrocystic disease group was similar to MPS group in terms of total IBP (p>0.05). Considering the localization of pain according to the quadrants where the pain was felt, 57.1% of the patients who felt pain in the upper quadrants were from MPS group (p=0.001) and 45.3% of the patients who felt pain in the lower quadrants were from cyclic mastalgia group (p=0.001). Myofascial pain was observed particularly in upper quadrants and almost all was unilateral; however, cyclic mastalgia was observed bilaterally in the majority, particularly in lower quadrants. Conclusion: Myofascial pain syndrome should be kept in mind as an extramammary disorder in the differential diagnosis of particularly unilateral upper quadrant mastalgia. It may be for the benefit of patients complaining of mastalgia with no primary breast disorder to be consulted with a physiatrist.